Technology-enabled hybrid cardiac rehabilitation: Qualitative study of healthcare professional and patient perspectives at three cardiac rehabilitation centres in England - Sarah Damery; Janet Jones; Alexander Harrison; Sebastian Hinde; Kate Jolly (PLoS ONE, 2025)
Coronary heart disease (CHD) is a leading cause of death in the UK. Clinical guidelines recommend cardiac rehabilitation (CR), including health education, cardiovascular risk reduction advice, physical activity and stress management components. However, uptake of standard in-person, group-based CR is only around 50%. Hybrid cardiac rehabilitation (CR), combining in-person and remote service delivery, may improve CR uptake and reduce inequalities in service access. This study used focus groups and semi-structured interviews to explore staff and patient experiences of using the Active+me REMOTE hybrid CR app, a cloud-based platform providing access to education modules, behaviour change support, live exercise classes, physical activity and health monitoring across three sites in the East of England. Twelve staff and six patients participated. Topic guides explored participants’ experiences of delivering or receiving hybrid CR, barriers and facilitators associated with the hybrid CR pathway, and implications for future implementation of Active+me REMOTE. Qualitative data were collected remotely, audio-recorded and independently transcribed. Staff data were analysed deductively, using the Consolidated Framework for Implementation Research (CFIR). Patient data were analysed inductively using thematic analysis. Despite some technical issues and governance delays, Active+me REMOTE was perceived as acceptable, convenient and allowed tailoring of support to meet patients’ needs and circumstances. Data upload from wearable devices (blood pressure monitors) allowed staff to monitor patients’ progress and empowered patients to direct their recovery. Staff initially felt they should screen patients to ensure that hybrid CR was offered to digitally literate, physically active individuals, although screening became less common as staff familiarity with the app increased. Findings suggest that effective implementation of hybrid CR requires system-level resource to facilitate governance approvals and embed hybrid CR delivery as standard care. Sufficient time must be allowed for staff training and to support patient enrolment to hybrid services. The study was registered on 3/7/2023 (ISRCTN320764).